Yield and chemical composition of foliage and branches of tropical tree legumes with different trunk diameters - Oliva-Hernández, Jorge; Molina-Salas, Isis; Vélez-Izquierdo, Alejandra; Castillo-Linares, Erika (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Erythrina americana Miller and Gliricidia sepium (Jacq.) Walp., are tree legumes presents on livestock farms in the tropical region, mainly on living fences. The goal of the study was to determine the influence of tree legume species (TLS), and of the trunk diameter at base tree (TDB), on production and chemical composition of foliage and branches at a similar regrowth age. The study was conducted in Tabasco, Mexico. Seventy-nine trees were used in a completely randomised design with a 2 X 5 factorial arrangement. The factors were TLS (E. americana y G. sepium), and TDB at 0.20 m height above ground level (D-5: 0.050-0.059 m; D-6: 0.060-0.069 m; D-7: 0.070-0.079 m; D-8: 0.080-0.089 m y D-9: 0.090-0.099 m). The production per tree of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and ash, of foliage and branches were the response variables. The STL x DBT interaction did not affect (P>0.05) the response variables studied in the foliage and branches. In foliage, the TLS and TDB affected the production per tree of DM, CP, ADF, and ash (P<0.01). G. sepium produced a greater amount of DM and the different components assessed than E. americana. An increase in TDB resulted in higher DM production and the components studied in foliage and branches. G. sepium produces foliage with higher CP and lower structural carbohydrate content than E. americana foliage.